2002
DOI: 10.1007/s00213-002-1101-7
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and its withdrawal alter feeding induced by paraventricular hypothalamic injections of neuropeptide Y in Sprague-Dawley rats

Abstract: These findings provide behavioral support that changes in PVN-NPY neurotransmission may play a functional role in the food intake and weight-modulating effects of NIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…However, in another study, hypothalamic NPY peptide was found to be increased after 14 days of low-dose (4 mg/kg/day) nicotine treatment, which reduced food intake by 19.5% in rats (Li et al, 2000), suggesting that the present treatment may have been too short to cause significant changes in NPY peptide. Furthermore, previously it was found that nicotine can directly inhibit the hyperphagia produced by exogenous administration of NPY into the PVN (Bishop et al, 2002), suggesting it is possible that the effects of brain NPY can be offset by nicotine or other elements in cigarette smoke. The effects of nicotine administration on NPY peptide in mice have not been documented previously.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, hypothalamic NPY peptide was found to be increased after 14 days of low-dose (4 mg/kg/day) nicotine treatment, which reduced food intake by 19.5% in rats (Li et al, 2000), suggesting that the present treatment may have been too short to cause significant changes in NPY peptide. Furthermore, previously it was found that nicotine can directly inhibit the hyperphagia produced by exogenous administration of NPY into the PVN (Bishop et al, 2002), suggesting it is possible that the effects of brain NPY can be offset by nicotine or other elements in cigarette smoke. The effects of nicotine administration on NPY peptide in mice have not been documented previously.…”
Section: Discussionmentioning
confidence: 99%
“…An antagonist against corticotropin releasing factor (CRF) prevented increased ICSS thresholds in mecamylamine-precipitated, but not in spontaneous nicotine withdrawal (Bruijnzeel et al 2007). Altered responsiveness to neuropeptide Y in the paraventricular area may be relevant to withdrawal-induced changes in appetite and weight gain (Bishop et al 2002). Finally, there is preliminary evidence of hormonal correlates of withdrawal, including altered corticosteroid stress response (Semba et al 2004) and changes in brain and plasma concentrations of various steroids, such as progesterone (Concas et al 2006).…”
Section: Serotonin and Other Transmittersmentioning
confidence: 97%
“…These factors should be taken into consideration in the design of future studies. (52) Conflicting findings have been reported, not only regarding the relationship between smoking and serum levels of leptin but also regarding the levels of other peptides that regulate food intake, such as NPY, (53) orexins (54) and ghrelin. (47) The parenteral administration of nicotine, as well as the administration of inhaled nicotine, has been shown to markedly reduce food intake in rats by inhibiting the synthesis of NPY, one of the hormones that increase appetite.…”
Section: Final Considerationsmentioning
confidence: 99%